The classification of invasive carcinoma of the breast. Issue 8 (August 2013) - Gannon, Louisa M; Cotter, Maura B; Quinn, Cecily M
The classification of invasive breast carcinoma assists diagnosis, allows for comparison of different patient groups in clinical trials and facilitates epidemiological analysis. For the individual patient, accurate tumor classification informs clinical decision-making with emphasis on assessment of prognosis and treatment formulation. Tumor grade is an independent prognostic indicator and is calculated by assessing specific tumor characteristics microscopically. The Tumor Node Metastasis staging system, produced by the American Joint Committee on Cancer Union for International Cancer Control, combines information about the primary tumor size, the status of the regional lymph nodes and the presence or absence of distant metastases at diagnosis to classify disease. In recent years, the use of gene expression profiling technology has led to the development of the molecular classification of breast cancer and has highlighted the importance of hormone receptor and HER2 oncogenic pathways, with particular reference to targeted chemotherapy. Tumor typing involves the identification of 'no special type' carcinoma with variable clinical, histological and molecular characteristics and 'special type' carcinomas that are usually associated with a particular set of prognostic and predictive indices. Some special type carcinomas have unique biological features that influence diagnostic investigation and clinical management.